ANALYSIS OF CRITERIA AFFECTING THE EFFECTIVENESS OF IMPLEMENTING SELF-MANAGED CONSTRUCTION PROJECTS BASED ON COMMUNITY EMPOWERMENT AND CONTRACTUALITY - Suprapto, Aki’; Wulandari, Esti; Tjendani, Hanie Teki (Transpublika Publisher, 2024)
With the dominance of top-down development, the aspirations of the community's ideas in every stage of construction development are not perfectly absorbed, resulting in community antipathy towards every government policy. Therefore, to recreate public sympathy, the government released a program to strengthen village governance and development (P3PD) or better known as the village fund program. The AHP (Analytical Hierarchy Process) method is used to analyze the results of the questionnaire so that the weight value of the criteria and sub criteria can be known as the basis for selecting the implementation of construction activities. Based on the results of the analysis, the weight value of the criteria can be found as follows: quality criteria are the main criteria in the selection of construction projects with a weight of 0.235, cost with a weight of 0.203, time with a weight of 0.192, community participation with a weight of 0.144, labor with a weight of 0.117 and administration with a weight of 0.110.